The European Commission and the integration of Europe : images of governance - Hooghe, Liesbet (Themes in European governance., 2001)
What kind of Europe does the European Commission want? Should the EU be supranational or intergovernmental? Should the Commission be Europe's government or civil service? Based on interviews with 137 top Commission officials, Hooghe finds that the Commission is no less divided on European integration than Europe's leaders and citizens.